KEMAMPUAN BERBAHASA INGGRIS MAHASISWA SEKOLAH TINGGI PARIWISATA NUSA DUA BALI YANG MENGIKUTI INTERNSHIP PROGRAM PADA INDUSTRI PARIWISATA DI BALI - Ni Kade Juli Rastitiati; Lukia Zuraida; Indah Kusumarini; Ratri Paramita; Teguh Hadi Sukarno; luh' Tri Lilasari (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2016)
The research aimed at knowing and analyzing the competence of English language of the students of Sekolah Tinggi Pariwisata Nusa Dua Bali (STPNB) who joined the internship training program in hospitality industries in Bali. To meet the research objectives, the questionnaires were delivered to 50 respondents. The other method utilized was interview to staff of tourism industries who supervised the students.The data were then analyzed quantitatively based on Likert Scale, and qualitatively on the basis of the theory and concept of English language competency. The research found out that the overall English language competence of STPNB's students who joined the internship training program was good. The specific results were that the competence ofspeaking and reading were good, while the competence of listening and writing were fair. The implication of these research findings are the English language teaching in STPNB has to provide more practice on listening and writing aspects.